2020
DOI: 10.1007/s00256-020-03588-5
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating rheumatoid and psoriatic arthritis: a systematic analysis of high-resolution magnetic resonance imaging features—preliminary findings

Abstract: Background Because of overlapping phenotypical presentations, the diagnostic differentiation of rheumatoid arthritis (RA) and psoriatic arthritis (PsA) remains challenging. Thus, this study aimed to examine the diagnostic value of distinct imaging features obtained by high-resolution 3-T MRI for the diagnostic differentiation. Materials and methods Seventeen patients with PsA and 28 patients with RA were imaged at high resolution using 3-T MRI scanners and a dedicated 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
1
6
1
Order By: Relevance
“…However, since tendon sheath runs near bones, pulleys, volar plates and other fibrous structures, the enhancement along the tendon sheath may indicate secondary tenosynovitis from classical/functional enthesitis. Hence, our results may coincide with the hypothesis that primary inflammatory sites of PsA are enthesis, which is different from RA [7].…”
Section: Discussionsupporting
confidence: 89%
“…However, since tendon sheath runs near bones, pulleys, volar plates and other fibrous structures, the enhancement along the tendon sheath may indicate secondary tenosynovitis from classical/functional enthesitis. Hence, our results may coincide with the hypothesis that primary inflammatory sites of PsA are enthesis, which is different from RA [7].…”
Section: Discussionsupporting
confidence: 89%
“…PsA from RA. Abrar et al 17 Recently, we reported that iodine uptake correlated with a scoring system for the local inflammatory lesions as well as scores of visual analog scale for pain in PsA. 16 However, iodine uptake did not correlate with PACE scores in our study.…”
Section: Phenotypic Overlap Sometimes Leads To Difficulties Distingui...contrasting
confidence: 70%
“…Phenotypic overlap sometimes leads to difficulties distinguishing PsA from RA. Abrar et al 17 . examined the images obtained from high‐resolution 3‐Tesla MRI scanners and a dedicated 16‐channel hand coil for 17 PsA patients and 28 RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Early PsA can be difficult to differentiate from early RA both clinically and with imaging. Abrar et al showed that with high-resolution MRI extracapsular inflammation was more common with PsA, while flexor tenosynovitis was associated with RA at the MCP joint [82]. Peritendinitis of the extensor tendon at the MCP joints where the tendon sheath is absent, thought to represent functional enthesitis between the metacarpal head and extensor digitorum tendon, is more common in PsA than RA [3].…”
Section: Psoriatic Arthritismentioning
confidence: 99%